Bioaktivitas Minyak Atsiri Daun Bandotan (Ageratum conyzoides) Terhadap Respon Fisiologis (Glukosa Darah Dan Tachiventilasi) Ikan Koi (Cyprinus carpio) [Bioactivity Essential Oil Of Bandotan Leaf (Ageratum conyzoides) On Koi (Cyprinus carpio) Physiological Responses (Blood Glucose And Tachiventilation) ] - Laksmi Sulmartiwi; Mardiah Rahma Umami; Moch. Amin Alamsjah; Sri Subekti (Jurnal Ilmiah Perikanan dan Kelautan, 2014)
Abstract Koi (C. carpio) is one of famous ornamental fish in Indonesia. Fish often be subject of change or stessor like physical, chemical and biology on culture. Stress in fish caused released cortisol hormone and cathecolamine hormone. Cathecolamine increase glicogenolisis, cardiovascular regulation and respiration fungtion. Blood glucose and tachiventilation (opercular movement) can indicate stress respon in fish. Essential oil of A. conyzoides have central analgesic activity. Analgesic drugs in vertebrae can reduce stress in fish. Essential oil shown inhibitory effect of GABA transminase, an enzime GABA (gammaaminobutryic acid) degradation which can provoking sedation. Sedation effect in fish reduce blood glucose and tachiventilation. Potency bioactive essential oil of bandotan leaf compound haven't been know in aquaculture. The potency based of LC50 (Lethal Consentration 50 %) value Purpose of this research determined effect of essential oil Ageratum conyzoides leaf on Koi (Cyprinus carpio) Phsycology Response (Blood Glucose and Tachiventilation) every 4 hours durung 24 hours and LC50-24 hours. Research was conducted at Laboratory of Faculty of Fisheries and Marine Airlangga University Surabaya. Research design used Completely Randomized Design and followed by Duncan's Multiple range test. Results of analysis of variance (ANAVA) from early observation and every 4 hours during 24 hours day showed that each treatment of essential oil Ageratum conyzoides leaf gave a significantly different effect on the blood glucose and tachiventilation (P <0.05). The highest average of blood glucose was found in D treatment at second observation (443,67 mg/dl) and the lowest was found in C treatment (60,67 mg/dl). The highest average of tachiventilation was found in D treatment at first observation (1730 bit/9 minute) and the lowest was found in A treatment (437,67 bit/9 minute) at early observation. LC50-24 hours essenial oil Ageratum conyzoides leaf is 34,047 ppm. Based on measurements of water quality, treatments was still viable and good to supported viability of Cyprinus carpio during research, water temperature range between 29-31oC, range of dissolved oxigen 4-6 mg/l, pH ranges 7,5-8,3 and 0,0060,27 mg/l on ammonia.